Optimizing Lecturer Performance Assessment through Web-Based Application Design and Deployment - Solly Aryza; Zulkarnain Lubis; Alkho Warizmi (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2026)
The evaluation of lecturer performance is a critical process in higher education, directly influencing academic quality, institutional reputation, and continuous improvement in teaching outcomes. Conventional evaluation methods, often paper-based or fragmented digital systems, face challenges such as inefficiency, lack of transparency, and limited accessibility. To address these issues, this research presents the design and deployment of a web-based application for lecturer performance assessment, aimed at optimizing the evaluation process through automation, standardization, and real-time data access. The system was developed using a structured software development life cycle (SDLC) approach, combining requirements analysis, database design, user interface prototyping, and iterative testing. Key features of the application include secure data management, multi-role access (administrators, lecturers, students), automated scoring mechanisms, and interactive dashboards for performance visualization. The evaluation of system usability was conducted using the System Usability Scale (SUS), achieving an average score of 82.5, which indicates high user acceptance and effectiveness. Results show that the proposed web-based system significantly improves efficiency by reducing evaluation processing time by up to 65% compared to manual methods. Furthermore, the integration of real-time analytics enhances decision-making for academic leaders in designing lecturer development programs. This research demonstrates that a well-structured web-based application can play a vital role in ensuring transparency, accountability, and continuous quality improvement in higher education institutions.Keywords: Lecturer performance evaluation, web-based application, higher education, system usability, academic quality assurance.